AB098. SOH26AB_0244. Robotic right hemicolectomy: a cohort study on outcomes of intracorporeal anastomosis vs. extracorporeal anastomosis - Khosravi, Zahra; Clifford, Siobhan; Fleming, Christina; Coffey, Calvin; Peirce, Colin (Mesentery and Peritoneum, 2026)
Robotic right hemicolectomy (RRH) is an established approach for right-sided colonic pathology. Extracorporeal anastomosis (ECA) remains standard for laparoscopic and some robotic surgeons, but the robotic platform readily facilitates intracorporeal anastomosis (ICA). This study aimed to compare outcomes in patients with colon cancer undergoing RRH, with ECA or ICA, in a tertiary hospital.